PROFIT PLANNING WITH BREAK EVEN POINT (BEP) METHOD : (Case Study on Mr. Kantak's Oyster Mushroom Planting Media Making) - Kiki Nurmala Fatmawati (JOSAR (Journal of Students Academic Research), 2018)
The cultivation of oyster mushrooms belongs to Mr. Kantak is located on Jalan Sulawesi, Klampok Village, Sananwetan District, Blitar City. This business produces baglogs of white oyster mushroom growing media and sells its own mushrooms. The researcher focused on the cost of making baglog only. The purpose of the study was to find out (1) How big is the Break Even Point (BEP) as a Profit Planning Tool in the Making of Mr. Oyster Mushroom Planting Media Kantak (2) How much is the amount of margin of safety in business Making Oyster Mushroom growing media owned by Mr. Kantak (3) How big is the planning of profits obtained in the business of making an oyster mushroom growing media mr. Kantak. Through the calculation of the break-even point in the cultivation of oyster mushrooms can be easily used to calculate the sales volume, where the calculation can be used as a calculation tool to determine the desired profit. In this study using quantitative methods. The data used in this study are primary data and secondary data. From the results of interviews and observations made, researchers obtained the data needed to complete the data needed. Secondary data obtained in the form of organizational structure, history and business profile. The results of this study indicate that the sale of baglog sales is a minimum of 1,564 units with a break-even price for making baglog 4000 of Rp. 2,268 and in the making of baglogs which suffered 12% damage received a price of Rp. 2,200. In calculating the break-even point of making 4000 planting media obtained a safety point of 61%. So that the profit planning obtained in making 4000 planting media is Rp. 4,304,062 and in the case of the deduction of 12% damage received a profit plan of Rp. 4,488,566